2008
DOI: 10.1002/chem.200700308
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Bis‐cyclometallated Iridium(III) Phenanthroline Complexes with Pendant Fluorenyl Substituents: Synthesis, Redox, Photophysical Properties and Light‐Emitting Cells

Abstract: We report the synthesis, characterisation, photophysical and electrochemical properties of a series of cationic cyclometallated Ir(III) complexes of general formula [Ir(ppy)(2)(phen)]PF(6) (ppy=2-phenylpyridine, phen=a substituted phenanthroline). A feature of these complexes is that the phen ligands are substituted with one or two 9,9-dihexylfluorenyl substituents to provide extended pi conjugation, for example, the 3-[2-(9,9-dihexylfluorenyl)]phenanthroline and 3,8-bis[2-(9,9-dihexylfluorenyl)]phenanthroline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 65 publications
4
69
1
1
Order By: Relevance
“…The photophysical, electrochemical, and theoretical studies showed that addition of the bulky groups does not affect the emitting excited state, in agreement with other reports. [182,183] LECs using these complexes exhibit a roughly sixfold increase in the EQE when compared with the archetype complex without phenyl and phenolic ether groups. Additionally, other important device parameters, such as turn-on time, luminance, and stability improved upon increasing the size of the bulky groups.…”
Section: Using Bulky Groupsmentioning
confidence: 96%
See 1 more Smart Citation
“…The photophysical, electrochemical, and theoretical studies showed that addition of the bulky groups does not affect the emitting excited state, in agreement with other reports. [182,183] LECs using these complexes exhibit a roughly sixfold increase in the EQE when compared with the archetype complex without phenyl and phenolic ether groups. Additionally, other important device parameters, such as turn-on time, luminance, and stability improved upon increasing the size of the bulky groups.…”
Section: Using Bulky Groupsmentioning
confidence: 96%
“…[182,183] The addition of bulky groups and high luminances (1000 cd m À2 at 3 V). Notably, there are limits in the use of large substituents because driving voltages tend to increase as a consequence of larger intermolecular separation.…”
Section: Using Bulky Groupsmentioning
confidence: 99%
“…The topologies of the molecular orbitals of Ir2 and Ir4 ( Figure S4) are identical to those of Ir1. Similarly to those of related ppy-based cyclometallated Ir complexes, [31][32][33] the HOMO is composed of a mixture of Ir III dπ orbitals (t 2g ) and phenyl π orbitals with little contribution from the pyridine rings of the cyclometallated ligands. As the family of complexes Ir1-Ir4 only differs in the diimine ligand, the energy of the HOMO remains almost constant along the series and is slightly more stable for Ir3 and Ir4 (Figure 6, b).…”
Section: Theoretical Calculationsmentioning
confidence: 97%
“…[32,34] The groups of both Bryce and Schanze reported that incorporation of π-conjugated substituents, such as fluorenyl and 4-ethynyl-N,N-dihexylaniline substituents on the N ∧ N ligand led to a mixture of 3 MLCT (metal-to-ligand charge transfer) and 3 π,π* characters in the lowest triplet excited state (T 1 state) and thus increased the T 1 lifetimes. [17,35] Our group also demonstrated that introducing the benzothiazolylfluorenyl (BTF) substituents to the N ∧ N ligand dramatically increased the T 1 state lifetimes for both Pt II diimine acetylide complexes [23] and heteroleptic Ir III complexes. [18,19,27] However, incorporation of the BTF motif into the C ∧ N ligands in the Ir III complex resulted in a reduced T 1 lifetime.…”
Section: Introductionmentioning
confidence: 94%